Pain Self-management Strategies in Patients With Cancer: A Qualitative Study. Issue 2 (March 2023) - Orujlu, Samira; Hassankhani, Hadi; Rahmani, Azad; Sanaat, Zohreh; Dadashzadeh, Abbas; Allahbakhshian, Atefeh
Abstract : Successful pain management in patients with cancer is a significant challenge, and paying more attention to patients' experiences of pain self-management strategies has particular importance. This study aimed to explore pain self-management strategies in Iranian patients with cancer. This qualitative study was conducted on 14 patients with cancer. Data were collected using semistructured interviews and analyzed through the Graneheim and Lundman content analysis approach. Two main categories emerged from data analysis: (1) psychological pain self-management strategies, and (2) behavioral pain self-management strategies. Psychological strategies included pain distraction techniques, spiritual tendencies, increasing social interactions and support networks, pain tolerance and self-control, and resistance to pain. Behavioral strategies included massage and touch, heat and cold therapy, opium ( Taryak in Persian) and tobacco use, herbal and home remedies, and proper diet.